The Function of CDA in Media Discourse Studies: Fungsi CDA dalam Studi Wacana Media - Widuna, Indah Ayu (Universitas Muhammadiyah Sidoarjo, 2018)
Discussing the period of critical in discourse analysis, it has appeared at the end of 90's in the variety of analytical conceptual frameworks and approaches. This paper focuses to find out how CDA has an important role in the ideologies, in other side observing the power of media discourse studies. This study reviewed ten journal articles for checking the ways and methods used CDA to invent the social phenomenon. It has been used to unmask many ideologies that have oppression to a group but keep giving the highest authority to a group that is positive images. While the social actors have their own ways of using CDA.